Transposition of scientific knowledge in teaching Mathematics to the blind (Research, Society and Development, 2021)
This study aimed to investigate the challenges and potentialities in the transposition of scientific language in the teaching of mathematics for students with visual impairment. The research has a qualitative approach and as a form of appropriation and perception of elementary themes for the effectiveness of the study, a literature review was carried out. In the absence of a vision, alternative means should be used in order to promote familiarization with the sciences and the construction of knowledge in a similar way to other students. It was found that there is a difficulty in transposing scientific knowledge to school knowledge due, above all, to the lack of specific manuals on how to perform them satisfactorily, due to the specificity of scientific language. Adding to this absence is the lack of preparation of teachers, schools, and the lack of teaching materials adapted as challenges to be overcome in order to transpose the scientific language to people with different learning needs.